2014
DOI: 10.18052/www.scipress.com/ilns.8.44
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chromium by Biosorption Method (Chitosan)

Abstract: Discharge of metal containing effluents into water has been a cause of major concern. Traditional treatment methods are proving to be ineffective and expensive. Chitosan was studied as a potential biosorbent due to its positive charge and relatively low cost. The study involves evaluating the metal binding performance of chitosan in a Polymer Enhanced Diafiltration (PEDF) system which uses an ultra filtration membrane to retain the chitosan which, in turn, binds the metal, thereby preventing passage into the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Amount of yield consumption by using different plastics without catalyst: It is observed that when a plastic material like polyethylene is used as solo material without the support of a catalyst, the yield is 74 % whereas in polystyrene material [13], the yield is about 82 %. When combination of plastics is used, the yield is about 66 % with less amount of residue [14] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Amount of yield consumption by using different plastics without catalyst: It is observed that when a plastic material like polyethylene is used as solo material without the support of a catalyst, the yield is 74 % whereas in polystyrene material [13], the yield is about 82 %. When combination of plastics is used, the yield is about 66 % with less amount of residue [14] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[17], showed increased pollution with heavy metals, especially Pb, in soil of battery factories in Al-Waziriyah-Baghdad has exceeded internationally permitted limit. [18], showed that irrigation with water contaminated with heavy metals leads to accumulation of these elements in soil and makes it polluted.Process of draining contaminated water is difficult and relatively expensive, and there are many traditional treatment methods that are usually ineffective and expensive [19], therefore, many new technologies that are considered natural bio-alternatives have been used for easy cleaning elements from polluted water by adsorption method using biomass adsorbent. Use of low-cost adsorbents for treatment of contaminated water is currently recommended because adsorbents are usually available in large quantities and are therefore cost-effective and inexpensive [20].…”
Section: Introductionmentioning
confidence: 99%
“…Natural occurrence materials are used as adsorbent for reduction. The effect of pH, dosing, contact time, isotherm has been also studied [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%